2016
DOI: 10.1590/0103-6440201600679
|View full text |Cite
|
Sign up to set email alerts
|

Study of Anatomical Relationship between Posterior Teeth and Maxillary Sinus Floor in a Subpopulation of the Brazilian Central Region Using Cone-Beam Computed Tomography - Part 2

Abstract: This study evaluated the anatomical relationship between posterior teeth root apices and maxillary sinus floor (MSF) on 202 cone beam computed tomography (CBCT) exams. The distance between the root apices and the MSF, as well as the MSF thickness of the cortical bone closest to root apices and furcation regions were measured. The vertical and horizontal relationships of the MSF with the molar roots were classified into categories adapted from the criteria proposed by Kwak et al. (14). The shortest distances be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
48
2
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 23 publications
11
48
2
8
Order By: Relevance
“…Searching the literature for studies discussing the proximity of maxillary molars roots to MSF using CBCT, several studies have been found but none of them was conducted on Egyptian subjects. Hence, as long as differences in ethnicity characteristics could invite diversity in such anatomical relationship 31 , it was mandatory to assess this relationship in Egyptian subjects to explore the similarity with the other examined populations.…”
Section: Discussionmentioning
confidence: 99%
“…Searching the literature for studies discussing the proximity of maxillary molars roots to MSF using CBCT, several studies have been found but none of them was conducted on Egyptian subjects. Hence, as long as differences in ethnicity characteristics could invite diversity in such anatomical relationship 31 , it was mandatory to assess this relationship in Egyptian subjects to explore the similarity with the other examined populations.…”
Section: Discussionmentioning
confidence: 99%
“…Map-reading strategy in CBCT images reduces problems associated to overlapping of anatomical structures (43). The navigation dynamics favors a precise identification of roots position, frequency of root canals, presence of the isthmus and apical foramina (53,54). The root apices of the maxillary posterior teeth and the maxillary sinus floor may present intimate relationship that favors development of inflammatory, infectious and/or traumatic alterations in the maxillary sinus (MS) or vice-versa (55)(56)(57)(58)(59).…”
Section: Endodontic Treatment Planningmentioning
confidence: 99%
“…The root canal filling material must be contained only inside the root canal, there is no way to justify its presence beyond the root canal (12,35,36,40,41). In mandibular and maxillary molars, it is necessary to take care to avoid lead filling materials into mandibular canal and maxillary sinus, due the proximity of these anatomic structures with root apexes (53,58).…”
Section: Root Canal Filling and Retreatmentmentioning
confidence: 99%
“…[12][13][14][15][16] Entretanto, não existem estudos que associem a proximidade dos dentes superiores posteriores com o seio maxilar em pacientes diagnosticados com sinusite maxilar.…”
Section: Discussionunclassified
“…Estrela et al 16 estudaram a relação anatômica entre os ápices dos dentes posteriores superiores e a mucosa do seio maxilar através da TCFC e observaram que a menor distância entre o assoalho do seio maxilar e os ápices dentários foi observada na raiz mesiovestibular do segundo molar e na raiz palatina do primeiro molar. A maior distância foi observada na raiz vestibular do primeiro pré-molar com diferença estatística significante.…”
Section: Proximidade Dos Dentes Com O Seio Maxilarunclassified